2022
DOI: 10.1002/ps.6960
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale evaluation of physical drift and volatility of 2,4‐D choline in cotton: a four‐year field study

Abstract: BACKGROUND: Cotton with resistance to 2,4-D choline, glufosinate and glyphosate allows over-the-top use of these herbicides for postemergence weed control. Nontransgenic cotton is highly responsive to low rates of 2,4-D, causing concern among farmers when the herbicide is applied near the crop. Injury to nearby cotton following application of 2,4-D choline is sometimes blamed on volatilization of the herbicide.RESULTS: A large-scale experiment was conducted in 2018-2021 to better understand causes of damage to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Most herbicides have injurious effects on crop growth, causing leaves to shrink, inhibiting plant height, and causing flowers and fruit to drop, all of which cause serious reductions in crop yield [31,32]. After exposure, crops tend to regulate their physiological and metabolic functions in order to convert herbicides into harmless compounds [33].…”
Section: Discussionmentioning
confidence: 99%
“…Most herbicides have injurious effects on crop growth, causing leaves to shrink, inhibiting plant height, and causing flowers and fruit to drop, all of which cause serious reductions in crop yield [31,32]. After exposure, crops tend to regulate their physiological and metabolic functions in order to convert herbicides into harmless compounds [33].…”
Section: Discussionmentioning
confidence: 99%
“…Te procedure is reliant on the pesticide's vapor pressure, and low vapor pressure pesticides stay on the surface for a longer period of time than those with high vapor pressure, which tend to volatilize quickly into the air [42]. Te rate of volatilization is also infuenced by external variables, including temperature and wind speed, and the rate of pesticide evaporation increases with increasing speed and temperature [43].…”
Section: Volatilizationmentioning
confidence: 99%
“…As the mist containing 2,4-D butylate travels, moisture in the droplets evaporates rapidly, leaving behind a gaseous herbicide that can be carried further by the wind. It has been observed that under wind force scales of 3 or 4, the drift can extend up to nearly 100 m, and under wind force scales of 6 or 7, it can reach distances of 1500 to 2000 m [29]. Additionally, 2,4-D butylate may volatilize and drift downwind for a second time within 12 days of initial application [29].…”
Section: Influence Of Chemical Class On Algal Toxicitymentioning
confidence: 99%